1987
DOI: 10.1111/j.1423-0410.1987.tb04898.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐Day Storage of Human Platelet Concentrates in 30 ml of Plasma or Artificial Medium1

Abstract: Optimal conditions for the storage of platelet concentrates were studied by changing 5 environmental parameters: bag composition (PL146 vs. PL732), volume of plasma (60 vs. 30 ml), anticoagulant (CPDA-1 vs. heparin), nutrient (glucose vs. fructose) and medium (plasma vs. artificial medium). A full bilevel factorial study was conducted to evaluate each variable alone and in combination with the other variables for their effects on platelet aggregation and release in response to single and pairs of stimuli. Sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Adams et al . [15] have suggested the PCs may be stored for 5 days with a volume as low as 30 ml without significant changes in vitro platelet characteristics that are believed to reflect platelet viability and hemostatic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adams et al . [15] have suggested the PCs may be stored for 5 days with a volume as low as 30 ml without significant changes in vitro platelet characteristics that are believed to reflect platelet viability and hemostatic function.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Four point six percent (3/64) of PRP-PC units and 51.6% (32/62) of BC-PC units had volume less than recommended in quality control parameters. Though 51.6% (32/62) of BC-PC units had volume less than 70 ml, but certainly higher than 40 ml, and various studies[1516] have shown that a volume >40 ml maintained the pH >6.2. Each platelet function and viability was preserved after 5 days of storage at room temperature with continuous agitation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the quality of stored platelets and for sal-vage of plasma, several additive solutions were introduced. Some revealed good preservation of basic metabolic parameters and in vitro functions of the platelets [3][4][5][6][7][8]. In contrast to glucose-containing storage media [7], several glucose-free additive solutions were developed in recent years that contained alternative fuels to minimize the production of lactate within the PC [5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The major choices available at present are to increase collection by plasmapheresis (Sekiguchi, 1996) or to improve recovery from standard blood donations. Loss of plasma during processing of standard blood donations is mainly associated with the preparation of platelet concentrates and is of two kinds: (i) plasma used to resuspend the platelets, which can be conserved by reducing the volume of the platelet concentrate (PC) (Adams et al, 1987) or by replacing plasma with a platelet storage medium (Whisson et al, 1993;Murphy et al, 1995) and (ii) plasma trapped in the red-cell concentrate (RCC) as a result of the slow first spin used to separate platelet-rich plasma (PRP). This second kind of loss is much greater than the loss due to platelet resuspension and has the further disadvantage that it is associated with a nonstandard low-haematocrit red-cell product.…”
mentioning
confidence: 99%